UPAYA PENINGKATAN PRESTASI BELAJAR MATEMATIKA DENGAN MENGGUNAKAN MEDIA INTERAKTIF WORDWALL PADA SISWA KELAS III SD NEGERI TASIKMADU PURWOREJO - Rizqina Anjarwati; Elisa Novita Fiky Megantari; Siti Maisaroh (ADIDAYA : Aplikasi Pendidikan dan Sosial Budaya, 2026)
Low mathematics learning achievement in the topic of plane figures is one of the problems identified among third-grade students at Tasikmadu Elementary School, Purworejo. This problem is caused by teacher-centered learning and the limited use of engaging learning media, resulting in students becoming less involved in the learning process. This study aimed to improve students' mathematics learning achievement through the implementation of interactive Wordwall media. The study employed a Classroom Action Research (CAR) method based on the Kemmis and McTaggart model, which was conducted in two cycles. The research subjects consisted of 10 third-grade students, comprising 5 boys and 5 girls. Data were collected through tests and observations. Test data were analyzed using descriptive quantitative analysis by calculating the mean scores and the percentage of students' learning mastery, while observation data were analyzed descriptively and qualitatively to support the research findings. The results showed that the average student score increased from 77 in Cycle I to 85 in Cycle II. This improvement indicates that interactive Wordwall media is effective in enhancing students' mathematics learning achievement in the topic of plane figures